(untitled) (Research, Society and Development, 2022)
Objectives: To analyze neonatal morbidity and mortality due to jaundice in Pernambuco from 2008 to 2017. Methods: This is a descriptive and ecological epidemiological study which studied the population composed of newborns whose mothers reside in Pernambuco, under 28 days old, born between 2008 and 2017. Through data collected of DATASUS, temporal analysis of the indicators of Neonatal Mortality due to Jaundice (TMNI) and Proportion of Hospital Admissions (PIH) were performed Results: Between 2008 and 2017, the TMNI rate in Pernambuco was 4.92 deaths per 100,000 live births and its early component was more important than the late one. Over time, the TMNI rate declined, replicating the Brazilian standard. As for the hospital admissions, jaundice corresponds to 23% of all hospital admissions in patients aged 0 to 27 days in relation to conditions originating in the perinatal period. Unlike TMNI, the PIH rate for neonatal jaundice showed a significant increase over the study period, showing a strong and inverse correlation between the two indicators. Conclusions: By giving visibility to neonatal morbidity and mortality rates due to jaundice, it is possible to identify opportunities for timely intervention reorientation of care practices, efficient strategies in reducing unfavorable outcomes.